Recent Empirical Analysis on Public Service Companies Transparency: Case of Italy - Banushi, Blerina; Rija, Maurizio (European Scientific Journal, ESJ, 2019)
In recent years the role of public services has acquired increasing relevance on account of the growing awareness of the importance of such services in the social and economic development of a country. This is determined primarily by the demand for quality and good value (for money) by an ever more sensitive public (which has brought under analysis the methods of traditional service providers, no longer seen as able to respond efficiently to the changing and diversified needs of society), the need to conform to EU directives and the effects of liberalization and from an internal perspective of the industrial and institutional reorganization of the public sector. After a description of the theoretical background, the present study is aimed to analyse the transparency of the public service companies listed on the Italian Stock Exhange. Given the fundamental role played by these companies, this sudy investigates the levels of total and partial disclosure and identifies the successful elements as well as those areas where improvements could be made. In particular, for the research conducted, an attempt was made to adopt an index capable of showing a measure of the quality of transparency undertaken by the case-study companies in the FTSE Italy Public Services Sector. In order to meet this aim, the work is based on an index of â€œcorporate e-governanceâ€ used by Gandia. Based on the variables considered in the analysis of the websites, no company provides total disclosure with maximum values; the company which offers total disclosure with the highest value is Enel (9.52) while Ergycapital has the lowest value (3.14). Research thus shows that, it is necessary to improve the quality of disclosure of the public utilities companies listed on the Italian Stock Exchange.